Inhibition of Casein Kinase 2 Protects Oligodendrocytes From Excitotoxicity by Attenuating JNK/p53 Signaling Cascade - Canedo-Antelo, Manuel; Serrano, Mari Paz; Manterola, Andrea; Ruiz, Asier; Llavero, Francisco; Mato, Susana; Zugaza, José Luis; Pérez-Cerdá, Fernando; Matute, Carlos; Sánchez-Gómez, María Victoria (Frontiers in Molecular Neuroscience, 2018)
Oligodendrocytes are highly vulnerable to glutamate excitotoxicity, a central mechanism involved in tissue damage in multiple sclerosis. Sustained activation of AMPA receptors in rat oligodendrocytes induces cytosolic calcium overload, mitochondrial depolarization, increase of reactive oxygen species, and activation of intracelular pathways resulting in apoptotic cell death. Although many signals driven by excitotoxicity have been identified, some of the key players are still under investigation. Casein kinase 2 (CK2) is a serine/threonine kinase, constitutively expressed in all eukaryotic tissues, involved in cell proliferation, malignant transformation and apoptosis. In this study, we identify CK2 as a critical regulator of oligodendrocytic death pathways and elucidate its role as a signal inductor following excitotoxic insults. We provide evidence that CK2 activity is up-regulated in AMPA-treated oligodendrocytes and CK2 inhibition significantly diminished AMPA receptor-induced oligodendroglial death. In addition, we analyzed mitogen-activated protein kinase (MAPK) signaling after excitotoxic insult. We observed that AMPA receptor activation induced a rapid increase in c-Jun N-terminal kinase (JNK) and p38 phosphorylation that was reduced after CK2 inhibition. Moreover, blocking their phosphorylation, we enhanced oligodendrocyte survival after excitotoxic insult. Finally, we observed that the tumor suppressor p53 is activated during AMPA receptor-induced cell death and, interestingly, down-regulated by JNK or CK2 inhibition. Together, these data indicate that the increase in CK2 activity induced by excitotoxic insults regulates MAPKs, triggers p53 activation and mediates subsequent oligodendroglial loss. Therefore, targeting CK2 may be a useful strategy to prevent oligodendrocyte death in multiple sclerosis and other diseases involving CNS white matter